(untitled) (AYUSHDHARA, 2023)
The progressive acceptance of Ayurveda and its medicines post-pandemic creates new beginnings. Ayurvedic medicines are ancient, and their resurgence is necessary. Earlier, it was believed that Ayurvedic medicines are safe for all. But past centuries, awareness regarding toxicities caused by them is well proliferated among populations. The Safety and efficacy related concerns of Ayurvedic herbo-mineral/metallic formulations need to be clarified for the globalization of Ayurveda. R&D in drug development, pharmacotherapeutics, pharmacovigilance sections need to be carried out. This article provides justifications on the safety and efficacy concerns through compiling research on various formulations.